Components and outcome of triple antibiotic paste and its application in endodontic infections - Alsharif, Ainaa Abdulmoeen; Qul, Khalid Abdulghani; Qahtani, Arwa Nasser Al; Alomem, Omar Ahmad; Albariqi, Ali Hassan; Alshahrani, Ameerah Mohammed; Rayes, Raghda Mansour; Alanazi, Abdulelah Hussain; Almutairi, Rakan Naif; Almuntashiri, Abdulaziz Abdulrahman; Houmady, Rahaf Abdullah (International Journal Of Community Medicine And Public Health, 2023)
In the field of endodontic therapies, the use of antibiotics, especially in the form of root canal medications, plays a pivotal role in ensuring successful treatment outcomes. This review examines the role of triple antibiotic paste (TAP) in such therapies, delving into its composition, application, and effects on endodontic infections. TAP, a combination of metronidazole, ciprofloxacin, and minocycline, targets the diverse microbial flora in odontogenic infections. Its local application within the root canal space proves more effective than systemic administration, significantly reducing microbial count and aiding in tissue regeneration and disinfection. However, the use of TAP is not without challenges, as it can cause tooth discoloration, particularly due to minocycline, and raise concerns about antibiotic resistance and long-term biocompatibility. This study, conducted through a comprehensive literature search, evaluates the efficacy of TAP, its impact on tooth structure, and its role in maintaining the vitality of diseased pulp. The findings highlight TAP’s significant role in endodontic treatments, emphasizing its benefits in achieving therapeutic goals while acknowledging the need for careful consideration of its drawbacks.